Halogen bonding and host–guest chemistry between N-alkylammonium resorcinarene halides, diiodoperfluorobutane and neutral guests - Fangfang Pan; Mohadeseh Dashti; Michael R. Reynolds; Kari Rissanen; John F. Trant; Ngong Kodiah Beyeh (Beilstein Journal of Organic Chemistry, 2019)
Single crystal X-ray structures of halogen-bonded assemblies formed between host N-hexylammonium resorcinarene bromide (1) or N-cyclohexylammonium resorcinarene chloride (2), and 1,4-diiodooctafluorobutane and accompanying small solvent guests (methanol, acetonitrile and water) are presented. The guests’ inclusion affects the geometry of the cavity of the receptors 1 and 2, while the divalent halogen bond donor 1,4-diiodooctafluorobutane determines the overall nature of the halogen bond assembly. The crystal lattice of 1 contains two structurally different dimeric assemblies A and B, formally resulting in the mixture of a capsular dimer and a dimeric pseudo-capsule. 1H and 19F NMR analyses supports the existence of these halogen-bonded complexes and enhanced guest inclusion in solution.